2013
DOI: 10.3389/fpsyg.2012.00609
|View full text |Cite
|
Sign up to set email alerts
|

Self Perceived Emotional Functioning of Spanish Patients with Amyotrophic Lateral Sclerosis: A Longitudinal Study

Abstract: Background: ALS is a neurodegenerative disease of the entire motor system that most frequently ends with respiratory arrest in few years. Its diagnosis and the rapid progression of the motor dysfunctions produce a continued emotional impact. Studies on this impact are helpful to plan adequate psychotherapeutic strategies. Objective: To assess and analyze: First: How the patients with ALS perceive their emotional health. Second: The emotional impact of their physical disabilities. Third: The physical disabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Existing research does not mention any relationship between a progressive deterioration of motor functions and disorders of emotional nature [42]. Some earlier publications noted 'the disability paradox' phenomenon, a term that refers to the alleged lack of relationship between the subjective perception of physical dysfunction reported by ALS patients and a decline in quality of life [43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Existing research does not mention any relationship between a progressive deterioration of motor functions and disorders of emotional nature [42]. Some earlier publications noted 'the disability paradox' phenomenon, a term that refers to the alleged lack of relationship between the subjective perception of physical dysfunction reported by ALS patients and a decline in quality of life [43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Among ALS patients, being a burden was a prevalent feeling as disease progression (Mora et al . ). A cross‐sectional survey found that SPB was significantly correlated with the physical function of ALS patients (Chiò et al .…”
Section: Introductionmentioning
confidence: 97%
“…Our study shows that the ALS patients presenting mild impairment of the articulatory system, Existing research does not mention any relationship between a progressive deterioration of motor functions and disorders of emotional nature [42]. Some earlier publications noted 'the disability paradox' phenomenon, a term that refers to the alleged lack of relationship between the subjective perception of physical dysfunction reported by ALS patients and a decline in quality of life [43][44].…”
Section: Discussionmentioning
confidence: 52%